PROSPEK PENGEMBANGAN USAHA AGRIBISNIS GULA AREN (Study Kasus Di Desa Patemon Kec.Bungatan Kab. Situbondo) - Bahrawi Bahrawi; Sulistyaningsih Sulistyaningsih; Sumarno Sumarno (Program Studi Agribisnis Fakultas Pertanian, 2015)
The research was determined the operating revenues of palm sugar, knowing palm sugar business development prospects in the Village of Patemon District of Bungatan. The method of determining the area of the research was purposive method because in the village of Patemon there are a lot of palm plants and there are 30 heads of families who do business with palm sugar making it easier to study. Results showed that the income of palm sugar producers in the Village Patemon District of Bungatan Regency of Situbondo favorably with averages revenue in a month Rp.1.764.000, -. Prospects for the development of palm sugar business is done in the Village of Patemon District of Bungatan Regency of Situbondo not feasible to be developed. Where in this prospect analysis B / C ratio to find the feasibility that will lead to the development prospects of palm sugar business. Based on the analysis of B / C ratio of the average obtained over a period of a month reached 0.28 so that the palm sugar business is not feasible to develop. Factors causing palm sugar business is not viable on a palm sugar prices are still low, the cost of purchasing palm juice and the amount of labor. For entrepreneurs should pay attention to the cultivation of palm sugar with the efforts of a simple way to get to a more modern way to get the maximum added value, improve marketing which usually only wait for customers who come marketed and sold in stalls / shops around the village Patemon increased sales to other areas such as traditional markets Bungatan, White Sand Situbondo sights even in the center by a product-by Situbondo that Patemon village can be recognized by people outside, to improve marketing can work well, note also that the product packaging palm sugar is made more attractive and looks more worthy to be sold and purchased society, this contributes to increase business because these products have long hereditary done and has even become a featured komuditi Village of Patemon District of Bungatan Regency of Situbondo.